Implementasi E-Modul Karier Berbasis UMKM Lokal Untuk Meningkatkan Minat Berwirausaha Siswa di SMA - Nur, Edil Wijaya; Saman, Abdul; Buchori, Sahril (Universitas Palangka Raya, 2024)
This study aims to determine the effectiveness of local UMKM-based E-Modules to increase high school students' entrepreneurial interest. Using a pretest-posttest one group design, this pre-experimental quantitative research involved 12 students who were randomly selected to take part in career guidance services with information materials from the Local UMKM-Based Career E-Module. Data analysis used descriptive analysis and hypothesis testing relying on the Wilcoxon Signed Rank Test. Results showed a significant increase in students' interest in entrepreneurship after the intervention, with statistical analysis confirming the effectiveness of the E-Module. In conclusion, contextualized education in career guidance, supports wider application to increase entrepreneurial interest among high school students. The main findings are in line with the SCCT theory, which explains that exposure to local MSME actor models can increase students' entrepreneurial interest. Future research suggestions should involve a larger and varied sample from different schools and different locations.